The Poly-cistronic miR-23-27-24 Complexes Target Endothelial Cell Junctions: Differential Functional and Molecular Effects of miR-23a and miR-23b - Jia Li; Yang Zhao; Ying Lu; William Ritchie; Georges Grau; Mathew A Vadas; Jennifer R Gamble (Molecular Therapy: Nucleic Acids, 2016)
The regulation of function of endothelial cell–cell junctions is fundamental in sustaining vascular integrity. The polycistronic microRNA (miR) complexes containing miR-23a-27a-24-2, and 23b-27b-24-1 are predicted to target the majority of major endothelial junctional proteins. We focus on miR-23a and miR-23b, and investigate the functional effects of these miRs on junctions. While miR-23a and 23b only differ by 1 nucleotide (g19) outside the seed region and thus are predicted to have the same targets, they function differently with miR-23a inhibiting permeability and miR-23b inhibiting angiogenesis. Both miRs target the junctional attractive molecule (tight junction protein 2) ZO-2 and the repulsive molecule junctional adhesion molecule C (JAM-C), although the inhibition of JAM-C by miR-23a is more profound than by miR-23b. The difference in potency is attributable to differences at g19 since a mutation of the t17, the g19 binding site of miR-23b in the 3′UTR of JAM-C restores identity. We also show that the pattern of expression of miR-23a and miR-23b and their targets are different. Thus, the paralogues miR-23a and miR-23b can have profoundly different effects on endothelial cell function due at least partially to selective effects on target proteins and differences in expression patterns of the miRs. This work exposes a hitherto unappreciated complexity in therapeutically targeting miRs.